A large, benign prostatic cyst presented with an extremely high serum prostate-specific antigen level. (8th January 2016) - Chen, Han-Kuang; Pemberton, Richard
Abstract : We report a case of a patient who presented with an extremely high serum prostate specific antigen (PSA) level and underwent radical prostatectomy for presumed prostate cancer. Surprisingly, the whole mount prostatectomy specimen showed only small volume, organ-confined prostate adenocarcinoma and a large, benign intraprostatic cyst, which was thought to be responsible for the PSA elevation.